Perception regarding Sexuality, Contraceptive and Teenage Pregnancy among Adolescent Studying in Secondary Schools in Palpa District - Nepal, Manju; Maharjan, Susan; Adhikari, Bimala; Adhikari, Bimala; Khanal, Laxmi; Nepal, Parbati (International Research Journal of MMC, 2021)
Adolescence is a period of both opportunities and threats. It is also a phase in life marked by vulnerability to risky sexual behavior and underprivileged reproductive health outcomes. The objective of this study was to assess the perception regarding sexuality, contraceptive and teenage pregnancy among adolescents studying in secondary schools in Palpa District. A cross sectional analytical study designed was applied. Total enumerative sampling technique was used to select 407 schools going adolescents in four selected school in Palpa district. Data was collected using self-administered questionnaire. Analysis was done using descriptive and inferential statistics with SPSS version 20. Findings showed that 56.51% of adolescents had favorable perception on sexuality, 51.84% of adolescents had favorable perception on contraceptive and 55.77% had favorable perception on teenage pregnancy. There were significant association between Sex, Grade, Ethnicity, Type of family of adolescent and level of perception on sexuality, contraceptive and teenage pregnancy where Chi-square p value is less than .05 at 5% level of significance. Based on the findings of the study, majority of adolescents had favorable perception towards sexuality, contraceptive and teenage pregnancy which suggests that adolescents were aware on sexuality, contraceptive and teenage pregnancy.